Optimization of loading sequence and rehandling strategy for multi-quay crane operations in container terminals. (August 2015) - Ji, Mingjun; Guo, Wenwen; Zhu, Huiling; Yang, Yongzhi
Graphical abstract: Highlights: This paper proposes an optimization strategy for the rehandling operations based on the lowest and the nearest stack strategy. This paper establishes a mathematical model to integrate the loading sequence and the rehandling strategy considering stowage plan for ships and yards. An improved genetic algorithm, the lower-bound and t -test for multi-quay crane operations are discussed. Abstract: In this paper, we consider the optimization of loading sequence and rehandling strategy in the terminal operation. We present an optimization strategy to minimize the number of rehandles, and establish a mathematical model to integrate the loading sequence and the rehandling strategy under the parallel operation of multi-quay cranes. Furthermore, we give an improved genetic algorithm to solve the model. We show the efficiency of the optimization strategy and algorithm by comparing them with previous strategies and heuristics.